Composite electroplating to enhance the GMI output stability of melt-extracted wires. (15th April 2016) - Liu, Jingshun; Li, Ze; Shen, Hongxian; Qin, Faxiang; Jiang, Sida; Du, Zhaoxin; Phan, Manh-Huong; Sun, Jianfei
Abstract: Impedance output stability of Co-rich amorphous wires depends largely on the wire-terminal-connection, which can be accomplished by composite electroplating towards a robust sensor application. The present experimental results indicated that Ni/Cu composite layer composed of Ni, Cu plating and passivating treatment show a homogeneous microstructure, and excellent surface wettability, weldability and thermal expansion coefficient matching under variable temperature of wire-terminal-connecting. The properties of composite electroplated layer are mainly influenced by cathode current density, electroplating time and electrolyte temperature. The inhomogeneous distributed clustering-regions, disproportionated reaction, tendency of hydrogen brittleness and crack have been reduced by optimized coactions of intermolecular Van der Waals force, inner diffusion and mechanical bonding of electroplated layer. Therefore, the wire-terminal-connection is able to effectively improve impedance output stability by minimizing the disturbance of stray capacity, decreasing radio-frequency wave emission and electromagnetic signal attenuation, and suppressing the destabilization or concussion. Graphical abstracts: Highlights: A robust wire-terminal-connection by Ni/Cu composite electroplating exhibits excellent TEC matching and GMI output stability. Impedance output stability firstly confirmed by using the voltage wave form of oscillograph to explain Z instant fluctuation. Results indicate Ni/Cu composite electroplating are useful for potential high-resolution GMI sensor applications.